An analysis of various wound washing methods and their efficacy in treating chronic wounds: A comprehensive review of existing literature - Rahmat Effan Fahri Mahendra; Asmat Burhan; Indah Susanti (Journal of Wound Research and Technology, 2024)
Background: Methods for treating wounds continue to evolve in response to the increasing number of wounds seen each year. Whether patients have chronic or acute wounds, proper wound care can improve their quality of life. One of the most effective ways to speed up the wound healing process is to wash it. As excessive or inappropriate washing procedures can cause trauma to the wound bed, it is important to tailor the washing method to the specific wound condition. Aims: Comparing the efficacy of different wound cleansing techniques for chronic wounds. Design and Methods: A literature review. This research study is a literature review using PI(E)O (patient, intervention/exposure, and outcome) to determine the keywords used in the search in several databases. The databases used were PubMed, Wiley Online Library, Science Direct and ProQuest. The keywords used were (Wound Cleansing Method OR Wound Cleansing Technique) AND (Acute OR Chronic Wound). Results: A total of 16,500 articles were identified, after screening for the last 5 years (2019-2024), in English, full text, duplication, and according to the title and abstract, 18 articles were obtained, and 9 articles were included in this study. The results of the literature search found nine articles describing the wound washing methods used by patients with acute and chronic wounds, including swabbing in 2 articles, and irrigation in 7 articles. Conclusion: Irrigation is the most widely used method, due to the reduced number of bacteria, short healing time, minimal pain and high satisfaction rate. In addition, the irrigation method can be used in conjunction with other methods